Hybrid Magnetoelectric Nanowires for Nanorobotic Applications: Fabrication, Magnetoelectric Coupling, and Magnetically Assisted In Vitro Targeted Drug Delivery. Issue 8 (12th December 2016) - Chen, Xiang‐Zhong; Hoop, Marcus; Shamsudhin, Naveen; Huang, Tianyun; Özkale, Berna; Li, Qian; Siringil, Erdem; Mushtaq, Fajer; Di Tizio, Luca; Nelson, Bradley J.; Pané, Salvador
Abstract : An FeGa@P(VDF‐TrFE) wire‐shaped magnetoelectric nanorobot is designed and fabricated to demonstrate a proof‐of‐concept integrated device, which features wireless locomotion and on‐site triggered therapeutics with a single external power source (i.e., a magnetic field). The device can be precisely steered toward a targeted location wirelessly by rotating magnetic fields and perform on‐demand magnetoelectrically assisted drug release to kill cancer cells.